Evaluation of Febrile Seizures in NGMC And Assessment of Risk Factors For Recurrences - KM, Roma; Pyakurel, Manita; Ranhotra, Anoop Singh; Kanodia, Piush; Ahmad, Shakeel; Gupta, Veena (Journal of Nepalgunj Medical College, 2018)
Background: Febrile seizures (FS) are commonly confronted pediatric emergencies in the age group of 6 months to five years. Recurrences of febrile seizures are common. The objective of this study was to evaluate febrile seizures and identification of risk factors for recurrence of febrile seizures in children. Methods: This is a prospective hospital based study conducted in the Department of Pediatrics at Nepalgunj Medical College from July 2015 to June 2016, between age group of 6 months to 5 years meeting inclusion criteria. A complete history, detailed neurological examination and necessary investigations were done. Statistical analysis was computed using Statistical Package for the Social Sciences (SPSS) 16 version. Results: A total number of 72 children with febrile seizure were included in the study. Among them 49 (68%) were males and 23 (32%) were females. Maximum cases i.e. 43(60%) were in the age group of 7 months to 2 years and p value was 0.02 followed by 20(27%) in the age group of 2 years to 3.5 years and minimum were in the age group of 3.5-5 years i. e 9(13%). Simple febrile seizure was seen in 45(63%) and complex febrile seizures was seen in 27(37%). Recurrence of seizure was present in 13(18%) patients. Most common precipitating factor for febrile seizure was upper respiratory tract infection seen in 51(71%) followed by lower tract respiratory infection in 8(11%), acute gastroenteritis in 5(7%) and others 8(11%). Generalized tonic clonic seizures (GTCS) were most common present in 56(78%) patients. Conclusions: Febrile seizures are common amongst male children. Risk of febrile seizures decreases with age. One fourth of children with febrile seizures are at risk for recurrence. Generalized tonic clonic seizures are found to be predominant type of febrile seizures. Most common risk factor for febrile seizure was upper respiratory tract infections (URTI). JNGMC, Vol. 14 No. 2 December 2016, Page: 30-33